New record of Theophilea subcylindricollis Hladil, 1988 in Bulgaria (Insecta: Coleoptera: Cerambycidae) - Tsvetomir Tsvetanov (Historia naturalis bulgarica, 2024)
Theophilea subcylindricollis Hladil, 1988 was recorded for the second time in Bulgaria. A single male specimen was found on 7 May 2023 in Vinarovo Village, Vidin Province, Northwestern Bulgaria. Photos of the specimen ex situ are presented.